The Restoration and Conservation of Islamic Monuments in Egypt - Salim A. Elwazani (International Institute of Islamic Thought, 1996)
This book is about the care of the Islamic architectural heritage in Egypt. The book's salient ideas amount to an argwnent for the necessity of care based on the implied quality of significance attached to monwnents and urban districts as material testimonies to the country's history and culture through successive Islamic periods. The argument is supported by a series of papers dealing with the causes of physical deterioration of these testimonies and the strategies and procedures for preserving them. That existing buildings endure deterioration in their structural and material integrity over time poses no question. Familiar climatic elements, such as temperature and humidity, as well as normal use, dictate an incessant rate of deterioration. But eminent dangers, especially for historic buildings, stem from the oppressive acts of humans and nature. Widespread industry, population growth, land development, and wars all contribute to hwnan-generated building threat and deterioration; floods, hurricanes, and earthquakes, on the other hand, spearhead a gamut of natural forces of building deterioration. Relishing the value of architectural heritage and recognizing the need for its protection have prompted many nations to develop plans and programs of protection. To clarify issues crucial to protection efforts, debate intensified, particularly in Western Europe and the United States, since the early years of the twentieth century. These issues revolved around such sweeping questions as why (rationale), what (scope), and how (means and methods) to protect historic buildings. The "why" debate resolutions shaped the philosophy of preservation, and such a philosophy shaped, in tum and at least in principle, the answers for the "what" and "how" questions. Architectural heritage protection endeavors entered the international arena during the 1960s. Worldly conventions, charters, and organizations came into existence in order to foster cooperation between world members in the area of preservation. This situation presented opportunities, often for the first time, for developing countries to initiate or strengthen preservation efforts at home. These opportunities were enhanced through programs of international bodies, such as the United Nations Educational, Scientific, and Cultural Organization (UNESCO) and the International Council on Monuments and Sites (ICOMOS). However, opportunities to strengthen ...